Ginkgolic Acid as a carbapenem synergist against KPC-2 positive Klebsiella pneumoniae - Song, Yuping; Zou, Yinuo; Xu, Lei; Wang, Jianfeng; Deng, Xuming; Zhou, Yonglin; Li, Dan (Frontiers in Microbiology, 2024)
The successful evolution of KPC in bacteria restricted the clinical practice of carbapenems. This dilemma deteriorated the prognosis of associated infections and hence attracted increasing attention from researchers to explore alternative therapeutic options. Here, we found that Ginkgolic Acid (C13:0) (GA) exhibited effective KPC-2 inhibitory activity, both in laboratory strain and clinical strain containing KPC-2. Its synergistic effect with carbapenems against KPC-2 positive Klebsiella pneumoniae (K. pneumoniae) was subsequently confirmed by checkboard minimum inhibitory concentration (MIC) assay, time-killing assay, disk diffusion method and live/dead bacteria staining analysis. Further explorations revealed that GA could competitively bind to the active pocket of KPC-2 with meropenem (MEM) via residues Trp104, Gly235 and Leu166. The secondary structure and functional groups of KPC-2 were subsequently altered, which may be the main mechanism by which GA exerted its KPC-2 activity inhibitory effect. In addition, GA was also found to synergise with MEM to disrupt membrane integrity and increase membrane permeability, which may be another mechanism by which GA reinforces the bactericidal ability of carbapenems. Our study indicated that GA was an excellent KPC-2 inhibitor which could prolong the lifespan of carbapenems and improve the prognosis of patients.